2019
DOI: 10.2147/opth.s209813
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diathermy for 23-gauge sclerotomy: a functional and morphologic study to avoid ocular hypotony</p>

Abstract: Purpose To evaluate diathermy to minimize sclerotomy leakage during small-gauge vitrectomy and prevent ocular hypotony. Methods This observational prospective study included 327 patients (327 eyes) who underwent diathermy to close the sclerotomy sites during 23-gauge pars plana vitrectomy (PPV). All patients were operated by a single surgeon (ED) and evaluated at 30 and 60 days postoperatively. Patients with glaucoma, topical/systemic steroids use exceeding 30 days, ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For instance, Horowitz et al, tried diathermy and demonstrated its efficacy. 4 Felfeli et al and Zhang et al, reported use of scleral needling for wound closure post-TSV. 20,6 Sridhar et al, report on the relative efficacy of plain gut sutures versus the more standard polyglactin sutures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Horowitz et al, tried diathermy and demonstrated its efficacy. 4 Felfeli et al and Zhang et al, reported use of scleral needling for wound closure post-TSV. 20,6 Sridhar et al, report on the relative efficacy of plain gut sutures versus the more standard polyglactin sutures.…”
Section: Discussionmentioning
confidence: 99%
“…This also leads to decreased conjunctival scarring, reduced post-operative inflammation and less postoperative astigmatism contributing to overall comfort for the patient. 4 Whereas TSV has its advocates, some complications have been noted in the form of hypotony and endophthalmitis resulting from poor wound closure. 5 Imperfect scleral wound closure can be quite common even if the recommended guidelines of using the angled-incision approach are used in addition to excellent conjunctival placement and appropriate massage of the surgical wound.…”
Section: Introductionmentioning
confidence: 99%
“…The second article was titled, “Diathermy for 23-gauge sclerotomy: a functional and morphologic study to avoid ocular hypotony”. 3 In this prospective study enclosing 327 patients (327 eyes), the diathermy technique proved to be safe and feasible to close 23-gauge sclerotomies. Boscia et al 4 also stated that the cauterization of the sutureless sclerotomies might prevent ocular surface fluid from penetrating the incisions and avoid leakage of intraocular fluid during the postoperative period.…”
mentioning
confidence: 88%
“…16, No. 5, May 18, 2023 www.ijo.cn Tel: 8629-82245172 8629-82210956 Email: ijopress@163.com for suturing [12][13][14] . Substitutes for suturing include application of tissue adhesives [15][16] , conjunctival cauterization [17][18] , and scleral needling [19] .…”
Section: Introductionmentioning
confidence: 99%